MENINGKATKAN AKTIVITAS DAN KETERAMPILAN BERPIKIR KRITIS MENGGUNAKAN MODEL MAGIC DENGAN PERMAINAN CITIZENSHIP MATCH MASTER SDN TELUK DALAM 1 - Risda; Diani Ayu Pratiwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The problem in this research is the low level of activity and critical thinking skills student. This is due to the lack of use of varied learning models and media and students not being able to solve problems. Efforts to overcome this are by using the MAGIC model and the Citizenship Match Master game. The aim of this research is to analyze increases in student activity and critical thinking skills. This research uses the type of Classroom Action Research (PTK). The research subjects were 20 students of the VA class at SDN Teluk Dalam 1 Banjarmasin. The research results showed that student activity at meetings 1 to 4 increased from 35% with criteria "less active" to 95% with criteria "very active". Critical thinking skills at meetings 1 to 4 increased from 30% with criteria "less skilled" to 85% with criteria "very skilled". Based on the findings, it is concluded that the MAGIC model with the Citizenship Match Master Game can increase student activity and critical thinking skills and it is recommended to use this model as a reference in using the learning model.